Decoding Employee Digital Performance: An in-Depth Literature Analysis - Wang, Guifang; Mansor, Zuraina; Yee, Choy Leong (UUM PRESS, 2024)
Digitalization has permeated into personal life and organizational operations, capturing significant interest from various organizations. They are uncertain about how to measure the impact of factors and metrics in the digital transformation process on Employee Digital Performance (EDP). This uncertainty poses challenges for decision-makers in assessing the feasibility of digitization and predicting employee performance outcomes. This study, employing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), conducted a comprehensive evaluation of 32 articles, providing influencing factors, performance indicators, metrics, and scales to fill this crucial research gap. The paper reviews the results based on the theoretical vantage points of the Results and Determinants (RD) and "Adaptive Enterprise Architecture" frameworks (EA). The research results indicate that, firstly, in terms of factors influencing employee performance, leadership types, HRM, and digital technology as independent variables significantly impact employee performance, with numerous studies highlighting the crucial role of digital technology. Furthermore, employee attitude and behavior variables, as important mediating variables, exist between organizational support factors and employee performance. Secondly, in the PI style assessment domain, the evaluation of Employee Performance emphasizes flexibility, job quality, and innovation capabilities, particularly highlighting the utilization of resources (i.e., improving job performance with digital resources). However, there is a research gap in the study of competitiveness and finance. Additionally, this study compares the differences in measurement between organizational digital performance and EDP. The research findings lay a solid foundation for further exploration of "digital design" and performance outcomes and provide direction for future studies